Hand Book - Olesker, Lizzie; Sachs, Lynne (punctum books, 2026)
Hand Book: A Manual on Performance, Process, and the Labor of Laundry is a collection of writings and images from a performance and film set within a neighborhood laundromat, a microcosm of service work within our urban reality. With a focus on the people who are paid to wash and fold, Hand Book explores the convergence of dirt, stains, money, identity, and desire. Informed by both theory and history, filmmaker-poet Lynne Sachs and playwright Lizzie Olesker construct a model for making a site-specific work incorporating both live performance and film. From conversations with workers in laundromats around New York City, they develop a play that magnifies forms of manual labor that often go unrecognized. The core of Hand Book is Sachs and Olesker’s hybrid play-script which grew out of documentary material they collected in New York City over several years. Within this theatrical construct, the actors themselves navigate the dynamic between their laundry worker characters and who they are in their own lives. Images also engage with text to create an evocative graphic experience. Turning a page becomes an interactive, quasi-cinematic encounter, calling to mind the intimacy of touching other people’s clothes, almost like a second skin, the textural care for things kept close to the body. Hand Book includes essays, interviews, memoirs, and poetry that look at the relationship between art and social engagement. Observation, historical research, and fiction intersect, creating a patchwork of “what is” with a speculative, imagined “what was.” Historian and author Tera Hunter speaks to the importance of The Washing Society, a group of 3,000 Black women laundry workers who organized in Atlanta in 1881 for better pay and working conditions. Feminist historian Silvia Federici engages in a conversation about the meaning of reproductive labor and its relationship to laundry. Two leaders of a grassroots organization share their experience of immigration and activism. A dancer creates a gestural map of her choreography. An actor deconstructs the charged significance of her Civil War-era costume. Ultimately, Hand Book: A Manual on Performance, Process, and the Labor of Laundry presents an illuminating dialogue between the documentary arts, feminism, film, immigration, labor history, and theater. Throughout, a playwright and filmmaker contemplate how art-making can alter our understanding of the social structures of city life. Sachs and Olesker’s short documentary film The Washing Society will be available via QR code upon release of the book.